СРАВНИТЕЛЬНЫЙ АНАЛИЗ ПЕРЕМЕННОГО МАГНИТНОГО ПОЛЯ НА ПОВЕРХНОСТИ РОТОРА ТУРБОГЕНЕРАТОРОВ С РАЗНЫМ ЧИСЛОМ ЗУБЦОВ СТАТОРА В РЕЖИМЕ НАГРУЗКИ - Милых , В.И.; Полякова , Н.В. (Інститут електродинаміки НАН України, Київ, 2014)
The method of calculating of the variable magnetic field is presented on the rotor surface of the synchronous machines. It is based on the multi-position numerical field calculations of the magnetic field in rotating of the rotor and the changing currents in the stator winding. This takes into account the real geometry of the electromagnetic system and the saturation of the magnetic core. A comparative calculation and harmonic analysis of the variable component of the magnetic induction are performed in the mode of the rated load for the two turbogenerators with a different amounts of teeth of the stator core. The proposed method is universal for different electric machines and modes of their excitation. References 10, tables 3, figures 5.